2019
DOI: 10.1063/1.5066226
|View full text |Cite
|
Sign up to set email alerts
|

Carrier reduction studies of type-II superlattice materials for very long wavelength infrared sensing

Abstract: There are continuing efforts to develop type-II superlattice (SL) materials for very long wavelength infrared (VLWIR) detector applications. However, the SLs have high residual electron background doping densities that depend on SL growth conditions, which lead to shorter minority carrier lifetime and lower performance parameters than theoretically predicted. In this study, the authors compare the technical advantages of using InAs/GaInSb over InAs/GaSb SL with respect to reducing the electron doping levels. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The semimetallic character and the semiconductor-semimetal transition of InAs/GaSb SL was studied experimentally well by transport and far infrared magneto-optical measurements by guldner et al [22]. We used the measured electron carrier density n as a function of the inverse of temperature by haugan et al [23], we determine the experimental band gap in the intrinsic domain by plotting nT -3/2 as a function of 1000/T. We found Eg= 95 meV, which is in agreement with 98 meV calculated at 300 K.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The semimetallic character and the semiconductor-semimetal transition of InAs/GaSb SL was studied experimentally well by transport and far infrared magneto-optical measurements by guldner et al [22]. We used the measured electron carrier density n as a function of the inverse of temperature by haugan et al [23], we determine the experimental band gap in the intrinsic domain by plotting nT -3/2 as a function of 1000/T. We found Eg= 95 meV, which is in agreement with 98 meV calculated at 300 K.…”
Section: Resultsmentioning
confidence: 99%
“…where kF 2D and kF 3D are the two dimensional and three dimensional Fermi wave vector respectively and n is the measured concentration of electron charge in the n(T) type sample [23]. The effective mass of electrons at the Fermi wave vector kF is m*E1(kF)=0.0284 m0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the photoluminescence (PL) properties of these structures are of interest to investigate the excitonic transitions and their correlation with the carrier recombination lifetime. The carrier lifetime of B80 ns was evaluated from the InAs/GaSb SLs by several researchers [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] by PL decay measurements and higher carrier lifetime is required for high performance photodetector. Haugan et al 36 demonstrated the long carrier lifetime of 140 AE 20 ns at B18 K for the InAs/ In 0.25 Ga 0.75 Sb SL structures compared to InAs/GaSb binary counterpart, and this enhancement was attributed to the strain-engineered ternary design and reduction of Ga-related Shockley-Read-Hall (SRH) recombination centers.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44] These effects can introduce the interfacial disorder that can affect the carrier recombination properties of InAs/GaSb heterostructures. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] During the tailor-made, tunable-wavelength infrared PD and low-power tunnel transistor structure design, 46 a precise Ga, In, As and Sb flux sequencing technique is necessary during the growth to avoid interface intermixing and atomic segregation, reduced active region defect density, lowered interface roughness, and interfaces free from interfacial disorder, which all will improve the carrier lifetime in InAs/GaSb materials. If each interface of strain balanced GaSb/InAs/GaSb heterostructure (GaSb on InAs is 0.62% compressive strain and InAs on GaSb is 0.62% tensile strain) introduces interfacial disorders during growth, then the SL structure of many interfaces will magnify the interfacial disorder and hence will affect both the optical as well as carrier recombination properties.…”
Section: Introductionmentioning
confidence: 99%